Measuring Equity: Creating a New Standard for Inputs and Outputs - Robert C. Knoeppel; Matthew R. Della Sala (Educational Considerations, 2013)
What is the appropriate measure of equity in student achievement? An emerging theme in the literature is the convergence of the standards movement and school finance litigation and reform.
Keywords: concept; education; adequacy; measuring; equity; student achievement; outcomes; inputs; outputs